The fundherentism: Susan Haack’s epistemology - Orozco Contreras, Richard (2013)
In this article, the author wishes to present Susan Haack’s epistemological proposal that aims to locate it in the middle between foundationalism and coherentism. The foundationalism asserts the existence of fundamental core beliefs. Instead coherentism believes consistency is enough to justifybeliefs. Haack sees insufficient both proposals and presents a new model to save the best of the other two: the foundherentism. The author explains that this proposal is directed towards two objectives: the problem of the justification of our beliefs and the problem of truth. Since the proposal itself is interesting, but it’s more interesting to see this new epistemology makes by a woman philosopher, with new visions and new perspectives as her contribution.